High-performance ultra-narrow-band green-emitting phosphor LaMgAl11O19:Mn2+ for wide color-gamut WLED backlight displays. Issue 19 (5th May 2022) - Wu, Zhangyue; Li, Chao; Zhang, Feng; Huang, Shixiang; Wang, Feijiu; Wang, Xiaoming; Jiao, Huan
Abstract : A high-performance ultra-narrow-band green-emitting phosphor LaMgAl11 O19 :0.28Mn 2+ ( λ em = 517 nm, FWHM ∼24 nm) is prepared by a solid-state reaction in air, which can be applied in a pc-wLED with wide color-gamut value of 131% NTSC and 97.8% Rec. 2020. Abstract : Explorations of narrow-band green-emitting phosphors have attracted much attention due to their great application potential in wide color-gamut wLED backlight displays. Herein, a high-performance narrow-band green-emitting phosphor LaMg0.72 Al11 O19 :0.28Mn 2+ (LMAO:0.28Mn 2+ ) was synthesized with a high activator doping content. The LMAO:0.28Mn 2+ green phosphor exhibits an ultra-narrow-band green emission peaking at 517 nm with an intriguing full width at half maximum of ∼24 nm. The LMAO:0.28Mn 2+ not only has a good internal quantum efficiency of 97.6% but also has an excellent low thermal quenching performance (92.3% peak intensity @423 K), especially an excellent resistance to color drifting (3.82‰ @423 K). A wLED device fabricated using LMAO:0.28Mn 2+, K2 SiF6 :Mn 4+ phosphors and a blue chip shows a wide color-gamut of 131% National Television System Committee (NTSC) standard, making LMAO:0.28Mn 2+ a highly promising candidate for wide color-gamut wLED backlights. The new strategy can be easily expanded to other systems and boost the development of efficient narrow-band emitting phosphors.